Fractures of the Zygomaticomaxillary Complex and Their Treatment: A Case Report - Bardhoshi Esat (Balkan Journal of Dental Medicine, 2016)
Fractures of the zygomaticomaxillary complex are the second most common of all facial fractures. Several fixation methods have been used over the years, including wire osteosynthesis, lag screw fixation, transfacial Kirschner wire fixation, titanium plate and screw fixation, and more recently, resorbable plating system. Internal fixation with titanium plates and screw provides the most rigid fixation and thus greater immobility of the fracture segments. The degree of immobilization created with titanium plates and screws also allows fixation at fewer anatomic points.